Efficacy of modified kidner procedure combined with subtalar arthroereisis treating adolescent type 2 painful accessory navicular with flexible flatfoot - Fang, Ke; Bi, Ting; Hong, Ao; Li, Xin; Gong, Haoli; Li, Bo; Li, Fanling; Wen, Jie; Xiao, Sheng (Frontiers in Pediatrics, 2023)
Purpose： To investigate the clinical efficacy of modified kidner procedure combined with subtalar arthroereisis in the treatment of adolescent type II painful accessory navicular with flexible flatfoot. Methods：From January 2018 to January 2022, 25 adolescent patients (40 feet) with painful type Ⅱ accessory navicular and flexible flatfoot admitted to our hospital were enrolled in the study, including 13 males (23 feet) and 12 females (17 feet). All patients underwent modified kidner procedure combined with subtalar joint arthrodesis. The Meary's Angle, the first metatarsal Angle of talus, the second metatarsal Angle of talus, Pitch Angle, talus tilt Angle, talonavicular coverage Angle, talus calcaneal Angle, and calcaneal Angle were measured on weight-bearing anteroposterior and lateral X-ray films before operation and at last follow-up. The American Orthopaedic Foot and Ankle Society (AOFAS) midfoot score and visual analogue scale were used to evaluate the improvement of foot function and pain.Results：All patients were followed up for average 17.4±2.6 months (12-24). The incisions of 25 patients healed by first intention. The weight-bearing anteroposterior and lateral X-ray films of the foot showed that the suture anchors did not pull out or break, and the foot arch did not collapse further. There was no screw withdrawal or secondary operation to remove the screw in all patients.At the last follow-up, the postoperative visual analogue scale score of the affected foot was significantly lower than that before operation (P < 0.01), and the AOFAS foot function score was significantly higher than that before operation (P < 0.01). At the last follow-up, the weight-bearing anteroposterior and lateral foot X-ray films showed that: The Meary's Angle, the first metatarsal Angle of the talus, the second metatarsal Angle of the talus, Pitch Angle, talar tilt Angle, talonavicular overbite Angle, talocalcaneal Angle, and calcaneal Angle significantly improved when compared with those before operation (P < 0.01).Conclusions：The modified kidner procedure combined with subtalar arthroereisis has a good clinical effect in the treatment of adolescent type Ⅱ painful accessory navicular with flexible flatfoot, which can effectively improve the pain symptoms, improve the foot function and imaging manifestations, and correct the flatfoot deformity.